Além da cárcere: uma análise da ressocialização no Complexo Penitenciário de Pedrinhas, sob o prisma do Programa Rumo Certo - Magalhães, Camila Maria Amorim Galvão de (2024)
This article starts from the following problematization: how does the São Luís Penitentiary Complex (Pedrinhas) lead to the resocialization of its inmates? What policies have been adopted, especially in the areas of education and work? To answer this questions, we sought to discuss some relevant concepts to the resocializing function of the custodial sentence and, in the subsequent topic, about the brazilian Criminal Law Enforcement. An overview of the city's prison system and the resocialization projects of its prisoners was drawn. Descriptive research was used, with a mostly qualitative approach, as well as the inductive method, and, as a research procedure, bibliographic and documentary research. Furthermore, the point of view of several theorists, whether from Law, Anthropology or Sociology, such as Foucault and Guilherme de Souza Nucci, and from brazilian positive law, such as the Federal Constitution of 1988 and the Criminal Code, are analyzed in this scientific work.